Evaluation of Erectile Function in Patients Undergoing Hemodialysis - (:unkn) unknown (GALENOS YAYINCILIK, 2021)
Objective: This study aimed to evaluate the erectile function in patients undergoing dialysis due to chronic renal failure and ascertain the causes of erectile dysfunction (ED). Materials and Methods: Patients undergoing hemodialysis admitted to our outpatient clinic with an erectile function evaluation between February and August 2019 were retrospectively investigated. The International Index of Erectile Function form erection scores, hormone levels, total dialysis durations, libido, nocturnal erection, and other additional diseases were recorded. Results: A total of 28 patients had all mentioned values. The mean age of patients was 58.6 (35-75) years. In the study group, only two of all patients (7.14%) had no erection complaints and both of them were under 40 years old. Approximately 93% of patients had ED and similar to 79% of this patient group was over 50 years old. The dialysis duration of patients ranged between 8-180 months. Patients' serum prolactin, glucose, testosterone, luteinizing hormone values, and erection scores were analyzed with Paired-Samples test. Glucose levels were found to be significant. Conclusion: The ED percentage is high, especially in patients over 50 years old with hemodialysis. The presence of diabetes in this patient group increased the erectile problems. Elevated prolactin alone was not detected as the cause of ED in patients undergoing dialysis. Further studies with larger series are necessary due to the limited number of patients in the study group; however, the current study suggested an investigation for ED in patients undergoing hemodialysis.
Keywords: Erectile dysfunction; hemodialysis; prolactin; DYSFUNCTION; TESTOSTERONE; PREVALENCE; MEN